Answers

The Brainliest Answer!
2016-01-30T16:27:09+05:30
M=+3 ; m=-3
when m=+3
    m=-v/u
    3=-v/u
    v=-3u
1/f=1/v+1/u
-1/20=-1/3u+1/u
1/u=1/3u-1/20
1/u=(20-3u)/60u
60=20-3u      [u cancels in the denominator]
-3u=60-20
-3u=40
u = - 40 / 3
u = - 13.33 cm

when m=-3
repeat the same steps when m = +3
then u=-80/3= 26.67 cm
1 5 1
because if u have two possible distances then v will also have
v is the distance of image formed, we have to find the distance of object not image
thank you
click "Thanks" :P
☺☺